The impacts of water infrastructure and climate change on the hydrology of the Upper Ganges River Basin - Bharati, Luna; Lacombe, Guillaume; Gurung, Pabitra; Jayakody, Priyantha; Hoanh, Chu Thai; Smakhtin, Vladimir U. (International Water Management Institute, 2011)
This study assessed the variability of flows under present and 'naturalized' basin conditions in the Upper Ganges Basin (UGB). Furthermore, the PRECIS regional climate model (RCM) was used to generate climate projections for the UGB, with subsequent simulations of future river flows. Results show that the annual average precipitation, actual evapotranspiration (ET) and net water yields of the whole basin were 1,192 mm, 416 mm and 615 mm, respectively. Precipitation, ET and water yields were found to be higher in the forested and mountainous upper areas of the UGB. On an annual average, present-day flows throughout UGB are about 2-8% lower than under naturalized conditions. Dry and wet season flows under climate change (CC) scenario A2 are lower than that under present climate conditions at upstream locations, but higher at downstream locations of UGB. Flows under CC scenario B2 are systematically higher and lower than that under CC scenario A2 during dry and wet seasons, respectively.